The Energy Level Conundrum of Organic Semiconductors in Solar Cells. Issue 35 (21st July 2022) - Bertrandie, Jules; Han, Jianhua; De Castro, Catherine S. P.; Yengel, Emre; Gorenflot, Julien; Anthopoulos, Thomas; Laquai, Frederic; Sharma, Anirudh; Baran, Derya
Abstract: The frontier molecular energy levels of organic semiconductors are decisive for their fundamental function and efficiency in optoelectronics. However, the precise determination of these energy levels and their variation when using different techniques makes it hard to compare and establish design rules. In this work, the energy levels of 33 organic semiconductors via cyclic voltammetry (CV), density functional theory, ultraviolet photoelectron spectroscopy, and low‐energy inverse photoelectron spectroscopy are determined. Solar cells are fabricated to obtain key device parameters and relate them to the significant differences in the energy levels and offsets obtained from different methods. In contrast to CV, the photovoltaic gap measured using photoelectron spectroscopy (PES) correlates well with the experimental device V OC . It is demonstrated that high‐performing systems such as PM6:Y6 and WF3F:Y6, which are previously reported to have negligible ionization energy (IE) offsets (ΔIE), possess sizable ΔIE of ≈0.5 eV, determined by PES. Using various D–A blends, it is demonstrated that ΔIE plays a key role in charge generation. In contrast to earlier reports, it is shown that a vanishing ΔIE is detrimental to device performance. Overall, these findings establish a solid base for reliably evaluating material energetics and interpreting property–performance relationships in organic solar cells. Abstract : The photovoltaic gap measured by ultraviolet and low‐energy photoelectron spectroscopy (UPS/LE‐IPES) gives the best correlation to device properties, enabling the prediction of maximum V oc . Cyclic voltammetry (CV)‐derived redox potentials are less meaningful for predicting the energetic landscape at the "donor"–"acceptor" interface.